Docentes e docência: caminhadas na educação a distância do IFAM - Ribeiro, Carmem Lúcia de Souza (2022)
The present dissertation entitled "Teachers and Teaching: walks in Distance Education at the Federal Institute of Amazonas/IFAM" aimed to investigate whether the pedagogical training offered to teachers who worked in the Lato Sensu specialization courses in Rural Education and History and African and Afro-Brazilian Culture developed through the Open University of Brazil (UAB) at IFAM, provided them with knowledge to face the challenge of planning and executing their DE classes. In addition, in the search to help teaching work in the field of distance education, this research brings as a final product, a book, in digital format, of the e book type, whose content addresses pedagogical and technical guidelines aimed at planning classes in this area. educational. The e-book is called “Planning classes in distance education”. Regarding the methodological procedures, we chose to use documental research, with a qualitative approach. Two data collections were carried out, the first being with a group of 10 (ten) professors who worked in the Lato Sensu Postgraduate courses in Education in the Field of African and Afro-Brazilian History and Culture offered by UAB at IFAM. In a second moment, 10 (ten) education professionals were invited to carry out the evaluation of the Educational Product generated through the research practice of this dissertation. Thus, an electronic questionnaire was used for data collection, created using the Google Forms resource. The participants' speeches were analyzed according to the principles of methodology and content analysis present in Bardin (2011). The results of the first survey showed some gaps to be filled, such as the large number of students per class and the difficulties in procedures to plan classes. In the second survey carried out, referring to the evaluation of the Educational Product, it showed a high level of acceptance of the e-book associated with this dissertation. The study concluded that the product generated in the course of the research practice represents an instrument that can guide pedagogical practices in distance education, as well as subsidize the improvement of teaching work in this teaching modality.